From Food to Mobility: Investigating a Screening Assay for New Automotive Antioxidants Using the Stable Radical DPPH. Issue 34 (13th September 2021) - Higgins, Clare L.; Filip, Sorin V.; Afsar, Ashfaq; Colquhoun, Howard M.; Hayes, Wayne
Abstract: By taking inspiration from the food industry, an assay was investigated as a potential screening tool to test the efficiency of new phenolic antioxidants. The method was based on the spectrophotometric measurement of the stable free radical 1, 1‐diphenyl‐2‐picryl hydrazyl (DPPH) which, in its radical form, has an absorbance maxima at 515 nm. The disappearance of this absorbance band, upon reaction with an antioxidant, was monitored to reveal the kinetic pathway of the reaction, which was defined simply as either fast, medium or slow. Adaptation of the assay was attempted for application to biofuels and oil‐based automotive fluids whereby the effect of polar and non‐polar solvents on the kinetics of the reaction was investigated. In addition, the stoichiometry of the radical scavenging reaction was also analysed to give an insight into the structure‐activity relationships of phenolic antioxidants. Abstract : A simple spectrophotometric assay involving monitoring the intensity of the absorbance maxima of the stable free radical 1, 1‐diphenyl‐2‐picryl hydrazyl (DPPH) has been developed to permit rapid assessment of the potential of new phenol antioxidants in biofuels and oil‐based automotive fluids in order to enhance their performance and operational lifetimes.